Genome Size Doubling Arises From the Differential Repetitive DNA Dynamics in the Genus Heloniopsis (Melanthiaceae) - Pellicer, Jaume; Fernández, Pol; Fay, Michael F.; Michálková, Ester; Leitch, Ilia J. (Frontiers in Genetics, 2021)
Plant genomes are highly diverse in size and repetitive DNA composition. In the absence of polyploidy, the dynamics of repetitive elements, which make up the bulk of the genome in many species, are the main drivers underpinning changes in genome size and the overall evolution of the genomic landscape. The advent of high-throughput sequencing technologies has enabled investigation of genome evolutionary dynamics beyond model plants to provide exciting new insights in species across the biodiversity of life. Here we analyse the evolution of repetitive DNA in two closely related species of Heloniopsis (Melanthiaceae), which despite having the same chromosome number differ nearly two-fold in genome size (i.e. H. umbellata (1C = 4,680 Mb), and H. koreana (1C = 2,480 Mb)). Low-coverage genome skimming and the RepeatExplorer2 pipeline were used to identify the main repeat families responsible for the significant differences in genome sizes. Patterns of repeat evolution were found to correlate with genome size with the main classes of transposable elements identified being twice as abundant in the larger genome of H. umbellata compared with H. koreana. In addition, among the satellite DNA families recovered, a single shared satellite (HeloSAT) was shown to have contributed significantly to the genome expansion of H. umbellata. Evolutionary changes in repetitive DNA composition and genome size indicate that the differences in genome size between these species have been underpinned by the activity of several distinct repeat lineages.